The Malaysian furniture industry: charting its growth potential - Ratnasingam, Jegatheswaran (Universiti Putra Malaysia Press, 2017)
The Malaysian furniture industry has come a long way since its humble beginnings in the mid-1980s. From a cottage-based industry, the industry has been transformed into a multi-billion ringgit export oriented industry, which outshines all other sub-sectors within the larger Malaysian timber industry. Through a series of Industrial Master Plans (IMPs), the government has played a pivotal role in incentivizing the industrial transformation process, through the provision of a steady industrial policy framework, with a strong focus on greater value-added products. In this context, it is thus not surprising that the Malaysian furniture industry has emerged as an important socioeconomic sector, providing employment to almost 80,000, while generating foreign exchange earnings in excess of US$ 2 billion in 2015. However, the rapid growth of the furniture industry has been fuelled by incremental capital inputs rather than through actual productivity gains. Therefore, increasing demand for factor inputs (especially raw materials and workforce) is apparent, despite the push towards a greater degree of automation and high technology machinery application. Analysis of the productivity data of the furniture industry, based on the Annual Manufacturing Survey, has shown that the trend of increasing factor inputs has been driving industrial growth, while other indicators such as labour productivity and capital productivity have remained stagnant, if not showing a decreasing trend. In fact, the research published by the author has revealed that the extent of value-addition and innovation within the Malaysian furniture industry has been on the decline over the years. Hence, the furniture industry in Malaysia remains as a large and well established contract furniture manufacturing hub, operating within the low-wage economy category. The shift from the original equipment manufacturing (OEM) strategy towards original design manufacturing (ODM) and original brand manufacturing (OBM) is not apparent within the industry. Innovations sourced from buyers and suppliers are often inclined more towards cost reductions and the focus is more on finding alternative raw materials rather than applying new processes or implementing a new design scheme. Therefore, in order to make the shift towards the manufacture of higher value-added, fashion-oriented furniture, several issues with regard to the factor inputs, policy directions, technology inputs and human capital development must be addressed, as research has revealed. This calls for a paradigm shift among the various stakeholders to ensure the sustainable and equitable growth of the furniture industry in the future. This lecture is aimed at reviewing the performance of the Malaysian furniture industry in terms of its growth and productivity perspectives. The review is based on the multi research work carried out by the author and his collaborators at the Faculty of Forestry, Universiti Putra Malaysia, with the aim of identifying, enhancing and strengthening the Malaysian furniture industry’s performance into the future, in an increasingly competitive global environment.